Bridge Scorekeeping Automation: An iOS Application to Improve Tournament Scoring Accuracy and Efficiency - Mahazoya, Aqilla Shahbani; Wiradinata, Trianggoro (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
Scoring in bridge tournaments is still largely dominated by traditional methods such as manual score sheets and specialized devices like Bridgemate. While widely used, these approaches present significant limitations—manual scorekeeping is prone to human error, and Bridgemate devices are often costly and not accessible to all organizers. To address these challenges, Bridge Team Comparator was developed as an iOS-based application offering a more accurate, efficient, and affordable scoring solution for bridge tournaments. Designed with a user-friendly interface for both novice and experienced players, the application supports real-time score entry, automatic calculation of International Match Points (IMP), and efficient result summaries. The development process adopted the Challenge-Based Learning (CBL) framework through the phases of Engage, Investigate, and Act, focusing on simplifying the bridge scoring process. User testing involved bridge athletes from Universitas Negeri Malang, Universitas Brawijaya, and the Sidoarjo bridge community. Results demonstrated a reduction in scoring errors by 8–36% and increased efficiency compared to conventional methods. In addition to offering a cost-effective alternative to commercial devices, the application contributes to the digital transformation of scoring systems in traditional sports. With potential for cross-platform development, Bridge Team Comparator opens new opportunities for broader adoption within the global bridge community.